PENINGKATAN LOYALITAS NASABAH TABUNGAN BNI TAPLUS CABANG JEMBER MELALUI RELATIONSHIP MARKETING - Paramita, Cempaka; Pahlevi, Mochamad Reza; Prasodjo, Adi (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2020)
The objective of this study is to examine and analyze the effect of relationship marketing that consists of dimensions of trust, commitment, communication, and conflict handling on the loyalty of the customers of Bank BNI in Jember, especially for the BNI Taplus Savings product. The population was all customers of BNI Taplus Savings in Jember. The sample used in this study was 105 respondents selected using a purposive sampling technique. Data were analyzed by multiple linear regression analysis. The results showed that, partially and simultaneously, trust, commitment, communication, and conflict handling, as part of relationship marketing, have a significant effect on the loyalty of the customers of BNI Taplus Savings in Jember. These results imply that the good relationship marketing programs conducted by BNI, by increasing trust and commitment, creating effective communication and conflict handling, will finally increase customer loyalty. Keywords: commitment, communication, conflict handling, loyalty, relationship marketing, trust